The relationship between the perception of reduced performance due to injury or illness and basic psychological need satisfaction in Norwegian youth elite handball: a cross-lagged panel analysis - Gjesdal, Siv; Bjørndal, Christian Thue; Luteberget, Live Steinnes (Scandinavian Journal of Sport and Exercise Psychology, 2022)
This study investigated the relationship between perceived reduction in performance due to injury or illness (RPII) and basic psychological need satisfaction in youth elite handball. Participants were 174 elite youth handball players between 15 to 18 years of age, from five different sport schools. It was a quantitative study, with two time points (one week apart), resulting in a crossed-lagged structural equation model. Competence and relatedness satisfaction were found invariant across the two time points, autonomy was not. The structural model showed good fit ((S- B χ²) = [df = 130, N= 174] = 182.327, p < .0017; CFI = .96; RMSEA = .05 [.03-.06], and SRMR = .08). Competence (β= .64, 95%CI: .51, .76), relatedness (β= .77, 95%CI: .66, .88) and RPII (β= .51, 95%CI: .37, .66) showed moderate temporal stability. When accounting for previous levels of the basic psychological needs, RPII negatively predicted competence (β= -.20, 95%CI: -.35, .83) and relatedness (β= -.16, 95%CI: -.30, -.01). Taken together, these findings suggest that experiencing RPII can have implications for basic psychological need satisfaction in youth elite handball, showing that factors other than psychosocial ones may play a role therein.